Pulmonary alveolar proteinosis - Chan, Adrian Kwok Wai; Takano, Angela; Hsu, Ann Ling; Low, Su Ying (Journal of Thoracic Disease, 2014)
We report a 68-year-old female who presented with chronic cough and progressive dyspnoea. Computed tomography of the thorax and subsequent bronchoscopy confirmed the diagnosis of pulmonary alveolar proteinosis (PAP), which was treated with whole lung lavage. This case is reported in view of the low incidence of PAP.